The relativity of ‘placebos’: defending a modified version of Grünbaum’s definition - Howick, J (Springer Netherlands, 2016)
Debates about the ethics and effects of placebos and whether ‘placebos’ in clinical trials of complex treatments such as acupuncture are adequate (and hence whether acupuncture is ‘truly’ effective or a ‘mere placebo’) rage. Yet there is currently no widely accepted definition of the ‘placebo’. A definition of the placebo is likely to inform these controversies. Grünbaum’s (1981, 1986) characterization of placebos and placebo effects has been touted by some authors as the best attempt thus far, but has not won widespread acceptance largely because Grünbaum failed to specify what he means by a therapeutic theory and because he does not stipulate a special role for expectation effects. Grünbaum claims that placebos are treatments whose ‘characteristic features’ do not have therapeutic effects on the target disorder. I show that with four modifications, Grünbaum’s definition provides a defensible account of placebos for the purpose of constructing placebo controls within clinical trials. The modifications I introduce are: adding a special role for expectations, insisting that placebo controls control for all and only the effects of the incidental treatment features, relativizing the definition of placebos to patients, and introducing harmful interventions and nocebos to the definitional scheme. I also provide guidance for classifying treatment features as characteristic or incidental.